Generating High-Order Transverse Patterns in Optically Pumped Semiconductor Lasers - Tuan, Pi-Hui; Hsieh, Yen-Hui; Tu, Chin-Wei; Lee, Chi-Chun; Tsou, Chia-Han; Liang, Hsin-Chih; Huang, Kai-Feng; Chen, Yung-Fu (IEEE journal of selected topics in quantum electronics, 2019)
High-order pattern formation in an optically pumped semiconductor laser (OPSL) under a selective pumping with varying spatial overlap between the pump beam and transverse modes is explored. In contrast to transverse pattern generation by off-axis pumped solid-state lasers where the mode order can be flexibly increased, experimental results reveal that the selective pumping fails to realize high-order mode operation in OPSLs when the pump-to-mode size ratio and pump power are insufficiently large. On the other hand, several high-order patterns belonging to the Hermite-Laguerre-Gaussian (HLG) modes are observed when scanning a large-ratio pump beam to specific positions on the gain chip. These HLG modes are experimentally confirmed to mainly originate from the transverse non-uniformity of present OPSL chip, while their structural features cannot be simply correlated with the pump scanning positions. Nevertheless, it is believed that the first-time observation of pure HLG modes under the large-ratio pumping can offer useful insights into the high-order pattern manipulation in OPSLs.